Learning About the Lived Experiences of Women with Autism from an Online Community. Issue 1 (2nd January 2017) - Haney, Jolynn L.; Cullen, Jennifer A.
ABSTRACT: The experience of being an adult female with an autism spectrum disorder (ASD) has been understudied in social work literature. The purpose of this study was to develop an understanding of females with ASD, from their perspective, by examining content from an online autism community Web site. Using a phenomenological approach, data analysis on content obtained from the forum revealed several themes about the women's experiences concerning the diagnostic process, managing and understanding symptoms, and the impact of ASD on their personal and work relationships. Implications for social work practice, including creating more effective services for females with ASD, are discussed.